2000
DOI: 10.1002/1522-2632(200011)85:5/6<697::aid-iroh697>3.3.co;2-s
|View full text |Cite
|
Sign up to set email alerts
|

Major Changes in Macroalgae Community Composition Affectthe Food and Habitat Preference of Idotea baltica

Abstract: Followed by the massive increase in the biomass of Pilayella littoralis, Fucus vesiculosus has almost disappeared in Kõiguste Bay, north-eastern Baltic Sea during 1995 -1998. Consequently, Idotea baltica, which previously fed on Fucus, switched to new food items -Furcellaria lumbricalis and Pilayella littoralis. Idotea grazed more Pilayella than Furcellaria whereas Furcellaria was highly preferred as a habitat. Maximum 2.2% and 4.7% of the production of Furcellaria and Pilayella were removed by grazing. We con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
49
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 33 publications
(52 citation statements)
references
References 13 publications
3
49
0
Order By: Relevance
“…We found, consistent with former fertilisation experiments, increased algal nitrogen and phosphorus content and a higher epiphytic algae to Fucus ratio on cormorant islands with an increased nutrient availability (Pedersen & Borum 1996, Kraufvelin et al 2006, Kraufvelin 2007, Råberg & Kautsky 2008. Contrary to previous studies investigating the effect of nutrient enrichment, on grazers in the Baltic Sea (Kotta et al 2000, Kraufvelin et al 2006, Kraufvelin 2007, Korpinen et al 2010) and chironomids in Lake Michigan, USA (Blumenshine et al 1997), not all invertebrates responded with increased abundance. Among the 5 invertebrate groups, only Jaera albifrons showed significantly higher density and biomass near cormorant islands with high nest densities.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…We found, consistent with former fertilisation experiments, increased algal nitrogen and phosphorus content and a higher epiphytic algae to Fucus ratio on cormorant islands with an increased nutrient availability (Pedersen & Borum 1996, Kraufvelin et al 2006, Kraufvelin 2007, Råberg & Kautsky 2008. Contrary to previous studies investigating the effect of nutrient enrichment, on grazers in the Baltic Sea (Kotta et al 2000, Kraufvelin et al 2006, Kraufvelin 2007, Korpinen et al 2010) and chironomids in Lake Michigan, USA (Blumenshine et al 1997), not all invertebrates responded with increased abundance. Among the 5 invertebrate groups, only Jaera albifrons showed significantly higher density and biomass near cormorant islands with high nest densities.…”
Section: Discussionsupporting
confidence: 90%
“…Fourth, we investigated if aquatic invertebrates responded to the high nutrient loads around cormorant islands by comparing the abundance and biomass of invertebrate grazers and chironomids from the 3 cormorant island categories with reference islands. Based on previous studies -both nutrient enrichment studies in the Baltic Sea (Kotta et al 2000, Kraufvelin 2007) and studies investigating the effects of seabirds on aquatic consumers (Bosman & Hockey 1986, Palomo et al 1999, Michelutti et al 2009) -we expected increased invertebrate abundances and biomasses near cormorant islands.…”
Section: Introductionmentioning
confidence: 98%
“…In concurrent with filamentous algal blooms the diversity of macroalgal species has significantly declined (Rönn-berg et al 1992;Kotta et al 2006). Our experiments and earlier studies have shown that among dominant macrophytes P. littoralis is the most rewarding food for mesoherbivores in the northern Baltic Sea (Kotta et al 2000Orav-Kotta and Kotta 2004). Hence, we may expect stronger competition for this resource in the study area.…”
Section: Discussionsupporting
confidence: 52%
“…However, this figure actually reflects a strong negative effect of G. tigrinus on G. salinus within P. littoralis. Following the increasing eutrophication the biomass of ephemeral algae especially P. littoralis have increased tremendously in the last decades and currently P. littoralis prevails in the northern Baltic Sea (Rönnberg et al 1992;Karez et al 2000;Kotta et al 2000;Lauringson and Kotta 2006). In concurrent with filamentous algal blooms the diversity of macroalgal species has significantly declined (Rönn-berg et al 1992;Kotta et al 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation